THE INFLUENCE OF WEB DESIGN, E-CUSTOMER SERVICE, SECURITY, AND FULFILLMENT TOWARD CUSTOMER SATISFACTION AND REPURCHASE INTENTION AT BUKALAPAK IN MEDAN - Fany; Alfonsius (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2025)
The study examines the factors affecting customer satisfaction and repurchase intention at Bukalapak, an e-commerce platform in Medan. Despite a wide variety of options, Bukalapak struggles with customer retention due to dissatisfaction with purchases and overall experience. Utilizing both primary and secondary data, researchers conducted questionnaires to Bukalapak’s customers in Medan. This study uses non-probability sampling, specifically purposive sampling and being analyzed with SPSS 25.00 and examined using multiple linear regression and linear regression. For data analysis, the findings reveal that web design and fulfillment significantly influence customer satisfaction, while e-customer service and security do not. Furthermore, customer satisfaction has a notable impact on the likelihood of repurchase intentions among Bukalapak customers.